Health-related Quality of life of Gaza Palestinians in the aftermath of the winter 2008–09 Israeli attack on the Strip - Abu-Rmeileh, Niveen M.E. (Oxford University Press, 2012)
Background: We document the health-related quality of life (HRQoL) of people living in the Gaza Strip 6 months after 27 December 2008 to 18 January 2009, Israeli attack. Methods: Cross-sectional survey 6 months after the Israeli attack. Households were selected by cluster sampling in two stages: a random sample of enumeration areas (EAs) and a random sample of households within each chosen EA. One randomly chosen adult from each of 3017 households included in the survey completed the World Health Organization Quality of Life instrument, in addition to reported information on distress, insecurities and threats. Results: Mean HRQoL score (range 0–100) for the physical domain was 69.7, followed by the psychological (59.8) and the environmental domain score (48.4). Predictors of lower (worse) scores for all three domains were: lower educational levels, residence in rural areas, destruction to one's private property or high levels of distress and suffering. Worse physical and psychological domain scores were reported by people who were older and those living in North Gaza governorate. Worse physical and environmental domain scores were reported by people with no one working at home, and those with worse standard of living levels. Respondents who reported suffering stated that the main causes were the ongoing siege, the latest war on the Strip and internal Palestinian factional violence. Conclusion: Results reveal poor HRQoL of adult Gazans compared with the results of WHO multi-country field trials and significant associations between low HRQoL and war-related factors, especially reports of distress, insecurity and suffering